Analysis of the Mutanaqisah Musyarakah Contract as a Solution for Home Ownership Financing in Islamic Banking - Yuli Nurhayati; Asyari Hasan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2022)
The need for residential houses is currently increasing. Islamic financial institutions, especially Islamic banking, offer a variety of products and services to face the needs of the community. Murabahah contracts are still a prima donna product in Indonesia, but murabahah has many weaknesses in its implementation. The presence of musyarakah mutanaqisah can be the best solution for property ownership for the community. The research method used is a qualitative approach with descriptive analysis and literature. This study aims to analyze the implementation and advantages of musyarakah mutanaqisah contracts in financing home ownership in Islamic banking. The results of the analysis show that the implementation of MMQ can be a solution for the community in fulfilling their prerequisites, but there are many things in musyarakah mutanaqisah that must be understood so that this product can run well in Indonesia. The benefits of musyarakah mutanaqisah contracts for customers are financing with relatively longer terms and additional spare parts that are more affordable.